IL-7 Abrogates the Immunosuppressive Function of Human Double-Negative T Cells by Activating Akt/mTOR Signaling - Allgäuer, Andrea; Schreiner, Elisabeth; Ferrazzi, Fulvia; Ekici, Arif Bülent; Gerbitz, Armin; Mackensen, Andreas; Voelkl, Simon (Journal of Immunology, 2015)
Recently, a novel subset of TCR??(+) CD4(-) CD8(-) double-negative (DN) T cells was described to suppress immune responses in both mice and humans. Moreover, in murine models, infusion and/or activation of DN T cells specifically suppressed alloreactive T cells and prevented the development of graft-versus-host disease after allogeneic hematopoietic stem cell transplantation. We demonstrated that human DN T cells, like their murine counterparts, are highly potent suppressor cells of both CD4(+) and CD8(+) T cell responses. After hematopoietic stem cell transplantation and other lymphopenic conditions, IL-7 plays an important role in the reconstitution, survival, and homeostasis of the T cell compartment. Because IL-7 was shown to interfere with T cell functionality, we asked whether IL-7 affects the functionality of human DN T cells. Intriguingly, IL-7 diminished the suppressive activity of DN T cells toward allogeneic CD4(+) effector T cells. Of interest, our studies revealed that IL-7 activates the Akt/mechanistic target of rapamycin (mTOR) pathway in human DN T cells. Importantly, selective inhibition of the protein kinases Akt or mTOR reversed the IL-7 effect, thereby restoring the functionality of DN T cells, whereas inhibition of other central T cell signaling pathways did not. Further analyses suggest that the IL-7/Akt/mTOR signaling cascade downregulates anergy-associated genes and upregulates activation- and proliferation-associated factors that may be crucial for DN T cell functionality. These findings indicate that IL-7 and Akt/mTOR signaling are critical factors for the suppressive capacity of DN T cells. Targeting of these pathways by pharmacological agents may restore and/or enhance DN T cell functionality in graft-versus-host disease.
EVALuna2:9259